Equipping CAR-Modified T Cells with a Brake to Prevent Chronic Adverse Effects - Wang, Wei; Wang, Yongsheng (Current Gene Therapy, 2012)
Genetical modification of T lymphocytes by chimeric antigen receptor (CAR), which has the affinity to tumor associated antigen (TAA), can redirect the normal T lymphocytes with tumor specificity. Through optimization of the CAR construct from first generation to third generation, the properties of these CAR-modified T lymphocytes, including, cytokines release, proliferative capacity, in vivo survival time, have been remarkably improved. These improvements accelerate the clinical applications of the CAR-modified T lymphocytes. Due to CD19, and CD20 specificity, CARmodified T lymphocytes have been clinically used to treat leukemia. Notably, T lymphocytes genetically engineered by Carl June group with CAR targeting to CD19 have expanded more than 1,000 folds by clearing all CD19 positive leukemia cells, even the normal B cells, which infiltrated in bone marrow, and survived for more than 6 months. This encouraging report demonstrates the overwhelming tumor-lytic ability of the CAR-modified T lymphocytes; it also raises the concern about the chronic toxicity. Here, we emphasize the safety concern when using the CAR-modified T lymphocytes. We also summarize strategies exploited to clear the genetically engineered T lymphocytes under an urgent condition, which increases the safety and optimizes the applications of the CAR-modified T lymphocytes.
Keywords: T lymphocytes